Semi-refined K-carrageenan: Part 1. chemical modification of semi-refined K-carrageenan via graft copolymerization method, optimization process and characterization of its superabsorbent hydrogel - Mohd Daud, Jamaluddin; Warzukni, Nor Shuhadah; Mohd Salim, Rosliza; Zuberdi, Ahmad Muzammil (Oriental Scientific Publishing Company (Bhopal), 2015)
This study was carried out for the preparation of superabsorbent hydrogel from semi-refined K-carrageenan originated from Kappaphycus alvarezii (Doty) Doty ex P. Silva through graft copolimerization method with acrylic acid. The reaction was carried out in an aqueous solution in the presence of N,N-methylene bis-acrylamide as a crosslinker and ammonium persulphate as an initiator. The effect of the amount of crosslinker, monomer, initiator and alkali on the swelling capacity of the hydrogel was investigated for optimum conditions. After preparing the desired hydrogel according to optimum conditions, the hydrogel was characterized by FTIR spectroscopy, SEM microscopy and swelling capacity measurement.